2018
DOI: 10.5114/aoms.2016.63149
|View full text |Cite
|
Sign up to set email alerts
|

The utility of Leventhal’s model in the analysis of the psycho-behavioral implications of familial cancer – a literature review

Abstract: IntroductionWe aim to highlight the utility of this model in the analysis of the psycho-behavioral implications of family cancer, presenting the scientific literature that used Leventhal’s model as the theoretical framework of approach.Material and methodsA systematic search was performed in six databases (EBSCO, ScienceDirect, PubMed Central, ProQuest, Scopus, and Web of Science) with empirical studies published between 2006 and 2015 in English with regard to the Common Sense Model of Self-Regulation (CSMR) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The utility of the CSM for understanding the psychosocial implications of physical illness has been demonstrated in different types of conditions (Hagger & Orbell, 2003) such as asthma (Achstetter, Schultz, Faller, & Schuler, 2019), cancer (Postolica, Iorga, Savin, Azoicai, & Enea, 2018), and brain injuries (Snell, Hay-Smith, Surgenor, & Siegert, 2013). In addition, there has been a growing interest in using the CSM in the context of mental illness (Antoniades, Mazza, & Brijnath, 2017;Scerri, Saliba, Saliba, Scerri, & Camilleri, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The utility of the CSM for understanding the psychosocial implications of physical illness has been demonstrated in different types of conditions (Hagger & Orbell, 2003) such as asthma (Achstetter, Schultz, Faller, & Schuler, 2019), cancer (Postolica, Iorga, Savin, Azoicai, & Enea, 2018), and brain injuries (Snell, Hay-Smith, Surgenor, & Siegert, 2013). In addition, there has been a growing interest in using the CSM in the context of mental illness (Antoniades, Mazza, & Brijnath, 2017;Scerri, Saliba, Saliba, Scerri, & Camilleri, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Becoming aware of their disease is difficult for patients diagnosed with lung cancer [16,17]. The disease carries many different connotations [39] and is sometimes compared to post-traumatic stress [19,20]. The study showed that lung cancer patients who perceived the disease at a low level as threat, loss, harm or significance experienced high levels of stress.…”
Section: Discussionmentioning
confidence: 99%
“…Coping styles are related to the process in which stress occurs and to many other factors which modify the stress relationship and which are often considered as variables [36,39]. Research has shown that the styles related to the fighting spirit, acceptance and positive re-evaluation were the most adaptive for recovering among cancer patients [40].…”
Section: From Coping Styles To Stressmentioning
confidence: 99%
“…Embase, Wiley Cochrane Central Register of Controlled Trials, and PubMed were systematically reviewed to identify clinical trials or observational studies published before July 18, 2019 (date of last search) following relevant guidelines [ 20 , 21 ]. The search string broadly included “Fatty Acids,” “Omega-3”, “Omega-6”, “Docosahexaenoic Acids”, “Eicosapentaenoic Acid”, “Linolenic Acids”, “Linoleic Acids”, “pufa”, “polyunsaturated*”, “type 1 diabetes”, “IDDM”, “T1DM”, “islet autoimmunity”, or “autoimmunity”.…”
Section: Methodsmentioning
confidence: 99%